Digital image correlation in dental materials and related research: A review. Issue 5 (May 2021) - Yoon, Sungsik; Jung, Hyung-Jo; Knowles, J.C.; Lee, Hae-Hyoung
Graphical abstract: Abstract: Objective: Digital image correlation (DIC) is a non-contact image processing technique for full-field strain measurement. Although DIC has been widely used in engineering and biomechanical fields, it is in the spotlight only recently in dental materials. Therefore, the purpose of this review paper is introducing the working principle of the DIC technique with some modifications and providing further potential applications in various dental materials and related fields. Methods: The accuracy of the algorithm depending on the environmental characteristics of the DIC technique, as well as the advantages and disadvantages of strain measurement using optical measurements, have been elaborated in dental materials and related fields. Applications to those researches have been classified into the following categories: shrinkage behavior of light-cured resin composite, resin-tooth interface, mechanical properties of tooth structure, crack extension and elastic properties of dental materials, and deformation of dental restoration and prosthesis. This classification and discussion were performed using literature survey and review based on numerous papers in the international journals published over the past 20 years. The future directions for predicting the precise deformation of dental materials under various environments, as well as limitations of the DIC technique, was presented in this review. Results: The DIC technique was demonstrated as a more effective tool to measure full-field polymerization shrinkage of composite resin, even in a simulated clinical condition over the existing methods. Moreover, the DIC combined with other technologies can be useful to evaluate the mechanical behavior of material-tooth interface, dentine structure and restorative and prosthetic materials with high accuracy. Three-dimensional DIC using two cameras extended the measurement range in-plane to out-of-plane, enabling measure of the strain directly on the surface of dental restorations or prosthesis. Significance: DIC technique is a potential tool for measuring and predicting the full-field deformation/strain of dental materials and actual prostheses in diverse clinical conditions. The versatility of DIC can replace the existing complex sensor devices in those studies.